HUBUNGAN KELEMBAGAAN ANTARA EKSEKUTIF DAN LEGISLATIF DALAM PROSES PENYUSUNAN DAN PENETAPAN APBD KOTA SEMARANG TAHUN 2016 - rifky setya ramandha; Warsito . .; priyatno harsasto . (Journal of Politic and Government Studies, 2017)
INSTITUTIONAL RELATIONS BETWEEN THE EXECUTIVE AND THE LEGISLATIVE OF PREPARATION PROCESS AND ESTABLISHMENT OF THE SEMARANG BUDGET 2016ABSTRACTOne key to governance become effective and efficient is a good budget management. An agency relationship between the executive and legislative in the preparation and adoption of the budgeting will create a scheme for a fluency of governance mechanisms in the region. But in reality, the determination of the budget does not always go without a hitch. Sometimes found differentiation of opinion regarding the decision to be assigned. Political aspects of the budget is more dominating than the bottom up aspects, participatory, and technocratic also important in planning and budgeting.The purpose of this study was to describe the form of institutional relations and on what basis the executive and legislative considerations in the process of preparation and adoption of Semarang city budget in 2016. The method used is a qualitative research method. The research instrument with interviews and documentation study conducted on certain sources.Results of research's found that in the planning process in the city of Semarang is often merely a formality. Authorities were mostly interested in the discussion budgeting phase, because at this budgeting phase more concerned about the cost calculation. The Executive do opportunistic behavior for the superiority of its information while the legislative use superiority powers of its advantages. Rationale used is that the regulation and the priority needs of the community. However the priority making, they found an executive opportunistic behavior on the formulation of programs and legislative behavior is not fully aligned to the constituents.Keyword: Agency Theory, Rational Choice, Budgeting.